Bone wax in the treatment of partial epiphysiodesis of distal femoral growth plate: Case report at 10-year follow-up - Basiglini, Luca; Aulisa, Angelo Gabriele; Bandinelli, Diletta; Toniolo, Renato Maria; Falciglia, Francesco (Frontiers in Surgery, 2022)
Growth plate is the weakest structure in the skeleton of a child and a frequent site of injury or fracture; physeal injuries represent 15% to 30% of all fractures in children. Of all growth plate fractures, the incidence of growth arrest and disorders is around 15%. This paper is about a female patient who, at the age of 5 years, was treated for a polytrauma that involved a complex lesion of the growth plates of the knee. 4 days after trauma she underwent closed reduction surgery and internal fixation with cannulated screws for femoral and tibial fractures of the growth plate. A 20° valgus deviation of the left knee was highlighted at the three-month post-operative clinical check-up as a supposed result of a growth disorder of the femur. It was therefore decided to re-hospitalize the girl with the diagnosis of valgus knee due to epiphysiodesis of the lateral portion of the femoral physis. In the operating room an open femoral de-epiphysiodesis was performed with a burr; the drilled hole was then filled with bone wax. At the 20-month post-trauma follow-up, the left knee was still valgus about 20 ° relative to the other side. During follow up a slow but progressive improvement in the axis of the lower limbs was noted. Clinical and radiographic control 10 years after the trauma showed a complete recovery of the axis of the lower limbs. In the initial stages the presence of bone wax in the area of de-epiphysiodesis allowed the stabilization of the deformity on the 20 ° of preoperative valgus. The interpretation of the growth cartilage activity occurred in an asymmetrical way such as to realign the femoral load axis, can be based on the different mechanical stimulus on the two knee areas due to the pre-existing deformity. There is no unanimous evidence in literature in terms of management of growth disorders resulting from this type of injury. Bone wax resulted effective filling the hole of de-epiphysiodesis in distal femoral growth plate and allowed to obtain the response of the growth plate and to advantage the recovery during time in young children.